Digitalisasi Pembiayaan: Atensi UMKM Dalam Memanfaatkan Pembiayaan Peer To Peer Lending - Novitasari Agus Saputri; Agustin Dwi Haryanti; Thoufan Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to analyze the attention and motivation of Micro, Small and Medium Enterprises (MSMEs) towards online funding that utilizes technology. Indonesia has issued a regulation through the Financial Services Authority (OJK) Number 77/POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services. This service is the provision of financial services to bring together lenders and loan recipients through an electronic system using the internet network. OJK regulations have given birth to several of these service providers. OJK recorded 164 (one hundred and sixty four) legal financial technology (fintech) companies developing in Indonesia. The fintech company managed to record 18,569,123 (eighteen million five hundred sixty-nine thousand one hundred twenty-three) borrower accounts. This service is able to channel funding of Rp. 81,497,051,000,000,- (eighty one trillion four hundred ninety seven billion fifty one million rupiah). Data and information are recorded on the OJK website, namely www.ojk.go.id. The results of this study have an R2 value of 15.3% which shows that the influence of risk variables, understanding of finance and the ease of using fintech on interest in using fintech in terms of financing, namely Peer To Peer Landing. This value is very small when compared to other influential variables. The value of 84.7% is most likely influenced by other variables